ARTI PENTINGNYA PENGELOLAAN LINGKUNGAN DALAM RANGKA MENANGGULANGI KERUSAKAN HUTAN OLEH MASYARAKAT - Ferdricka Nggeboe (Jurnal LEX SPECIALIS, 2012)
Abstract Forests are not only ecological but also used to function as a source of livelihood. In the forest, the people have the perception that they are not part of forest management institutions that are not bound to the rules of forest management institutions. This perception is certainly wrong, because the prevention and control of pollution and degradation must be addressed seriously and are responsible not only government but community participation. With the enactment of Law No. 19 of 2004 as a replacement for the Law No. 41 Year 1999 on Forestry. In it has arranged a variety of things, including the rights and obligations of communities in forest conservation. Key Note : Management, Protection and Preservation